(untitled) (Latakia University Journal -Medical Sciences Series, 2021)
Purpose: To define the relation between pain after trans Transepithelial Photorefractive Keratectomy and the following variables: gender, Spherical Equivalent, Tear film Break up Time and corneal thickness. Methods: 236 eyes of 120 patients were included in this study, patient’s information were gathered including gender, spherical equivalent of the corrected refraction errors and the corneal thickness was measured using SIRIUS topographer, we also calculated the tear break up time before surgery and asked the patients to evaluate their pain level on the day of surgery and on the three days after using Numerical Pain Rating Scale – NPRS. Results: The mean pain degree on the day of surgery was (5.6±2.5), and on the first day after surgery (3.5±2.2), and it dropped significantly at the end of observation period, we didn’t find any statistically important correlation between pain and the following variables: gender, spherical equivalent, and corneal thickness in all time points. We found negative correlation between pain and tear break up time in all the time points of observation period with statistically important differences, where when the tear breakup time was short the pain severity increased and the relation was more obvious at the first day after surgery (p=0.0001). Conclusion: The patients that have a short tear break up time are exposed to more severe pain after trans PRK than the people who have a normal tear break up time, and we didn’t find any relation between the pain and the following variables sex, spherical equivalent, and the corneal thickness.